Kryzys w strefie euro - Kundera, Jarosław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The main goal of the chapter is to distinguish the causes of the euro crisis and the methods of its overcoming. The work examines the reasons of crisis and anticrisis policies in four countries of the euro zone the most affected by the economic crisis. Stands out for several reasons: bubble in the real estate market, global structural imbalances, imbalance in trade between the partners of the euro area, the growth of wages compared with Germany, excessive debt, monetary policy and low interest ECB interest rates, the lack of proper coordination between fiscal policy and national fiscal. Factors that lying behind the Euro crisis is not the wrong theory of optimum currency area, but the fact that economic policies of the member states are not suited to the fiscal and debt discipline. Author distinguished three scenario for euro area development: break up and to come back to national currencies, limit euro area to an optimal optimum currency area and institutional reform in the EU. Institutional reforms seems to be the least costly alternative. In the short run it requires that ECB will assume the function of the lender of last resort. In the long run it requires proper coordination between common monetary policy and fiscal policies in member states.
Keywords: coordination of monetary and fiscal policy; the economic crisis in Greece, Ireland, Portugal and Spain; banking union; structural policy; the public debt; budgetary deficit; austerity program